Management of Carious Pulp Exposure in Vital Permanent Teeth: An Evidence-based Clinical Practice Guideline - Saeed Asgary; Sara Ehsani; Raheleh Hassanizadeh; Armin Shirvani (Regeneration, Reconstruction & Restoration, 2016)
Introduction: Annually ~2 million permanent teeth are lost in public dental clinics in Iran. Many of these losses are caused by difficulties in provision of timely root canal treatment (RCT) or their low quality. The present guideline aimed to find and recommend the best treatment options for management of vital permanent teeth with carious exposure. Materials and Methods: The guideline domain was  examined  and  treatment  options  were  determined  as  scenarios  comprised  of  indications  and  possible  interventions. Two main indications including carious pulp exposure with or without irreversible pulpitis in open-apex and in closed-apex permanent teeth were included. Nine treatment options were found for each indication based on the available literature. Exhaustive search was performed to find the current evidence and the retrieved studies were critically reviewed. Treatment options and their supporting evidence were extracted. Search for the side effects and benefits of each treatment option was also performed. The expenses regarding each treatment were then determined and treatment options with Level of Evidence (LOE) I and LOE II evidence were presented to an expert panel for each indication. Each clinical scenario was examined and rated by each member considering six aspects: effectiveness of the intervention, costs, side effects, side benefits, applicability of the scenario and generalizability of the treatment. The best scenarios were chosen based on the expert panel ratings and the recommendations were extracted. Results: Based on the present guideline, full pulpotomy with calcium enriched mixture (CEM) cement is recommended in vital permanent teeth with open- or closed-apex, with or without irreversible pulpitis, following carious pulp exposure (Grade A recommendation). Conclusion: Adherence  to  the  present  guideline  may  help  preserve  pulp  vitality  and  decrease  the  risk  of  loss  of  vital permanent teeth with carious pulp exposure